Analysis of Governance System and Authority Distribution in DKI Jakarta: a Study of Government Structure and Electoral System - Uzdah , Nadya; Salsabila, Vivia; Saputra, Kristo; Dharmaputra, Mochamad Isa; Santa, Regina; Yosephine; Christanta, Febe; Natalia, Astrid Genius; Evani, Yessi; Limbong, Yohana Ditia (Universitas Sumatera Utara, 2024)
Local government is the implementation of government affairs by the provincial government and the Regional People's Representative Council according to the principle of autonomy and duties assistance with the principle of the broadest possible autonomy within the system and regulations of the Unitary State of the Republic of Indonesia as intended in the 1945 Constitution of the Republic of Indonesia. In Indonesia itself, several autonomous regions have their specialties, one of which is the Provincial Government of the Special Capital Region of Jakarta, which carries out government affairs according to the principles of autonomy and assistance duties with the broadest economic principles as intended in the 1945 Constitution of the Republic of Indonesia. The research method employed in this study is the juridical normative method, which analyzes the applicable laws and norms related to the structure of regional government and the electoral system.